A review of nasopharyngeal swab and saliva tests for SARS‐CoV‐2 infection: Disease timelines, relative sensitivities, and test optimization. Issue 4 (6th June 2021) - Roque, Marylin; Proudfoot, Kevin; Mathys, Vadim; Yu, Sophie; Krieger, Natalie; Gernon, Thomas; Gokli, Kash; Hamilton, Stanley; Cook, Colin; Fong, Yuman
Abstract: Testing is an essential part of containment of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic. This review summarizes studies for SARS‐CoV‐2 infection and testing. Nasopharyngeal samples are best at sensitivity detection, especially in early stages of disease and in asymptomatic individuals. Current swab processing involves a 100‐ to 1000‐fold dilution of the patient sample. Future optimization of testing should focus on using smaller volumes of viral transport media and swab designs to increase comfort and increased viral adhesion.